(untitled) (Journal of Basic and Applied Sciences, 2015)
The present study was carried out during the autumn season in 2002-2003 in the crop sciences department laboratories, agriculture college, Tripoli University. Seeds of six tobacco varieties were exposed to four different levels of gamma radiation namely 0, 100, 200 and 400 Gry. The irradiated seeds were planted in sterilized glass Petri dishes in a completely randomized design. As a preliminary study, seed germination speed and percentage were studied starting in the seventh day to the fifteenth day from planting. From the results of the statistical analysis, there were clear and significant differences between the varieties in percent germination and days to germination. Also there was a clear and significant effect of the three way interaction, indicating the dependence percent germination and speed of germination on time in days and on radiation levels.